TINJAUAN YURIDIS TERHADAP PERKAWINAN BEDA AGAMA BERDASARKAN UNDANG-UNDANG NOMOR 1 TAHUN 1974 - Bing Waluyo; Wiwin Muchtar Wiyono; Aris Priyadi (LPPM STIH Awang Long, 2023)
In Article 2 paragraph 1 of the Marriage Law it is stated that marriage is valid if it is carried out according to the laws of each religion and belief. In the Explanation of Article 2 paragraph 1 of the Marriage Law it is stated that no marriage is outside the law of each religion and belief in accordance with the 1945 Constitution. Thus according to law, marriage must take place according to the law of each religion and belief. If the marriage is carried out outside or contrary to the laws of each religion and belief, then the marriage is invalid. The words